Locations & languages: Towards multilingual user movement analysis in social media - Wang Y.; Pozi M.S.M.; Siriaraya P.; Kawai Y.; Jatowt A. (Association for Computing Machinery, Inc, 2023)
Carrier mobility; Location; Heterogeneous data; Micro-blogging platforms; Mobility pattern; Multilingual; Multilingualism; Natural phenomena; Research proposals; Twitter; Social networking (online)